An Exploration of Kindergarten Teacher’s Mastery Motivation in Yogyakarta - Rolina, Nelva; Agustiningsih, Rini; Muthmainah, Muthmainah; Hayati, Nur; Wulandari, Rina (Jurnal Pendidikan Anak, 2025)
Mastery motivation is an internal drive to master challenging tasks and achieve competence. In the context of early childhood teachers in Indonesia, studies on this topic remain limited. This research aims to explore the level of mastery motivation among kindergarten teachers in the Special Region of Yogyakarta and identify the factors that influence it. A qualitative, exploratory approach was employed, involving in-depth interviews, non-participant observations, and document analysis with 15 teachers representing the five districts in Yogyakarta. Thematic analysis was conducted to identify patterns of meaning and characteristics of mastery motivation. The findings reveal three levels of mastery motivation high, moderate, and low with most teachers falling within the moderate to high categories. Teachers with high motivation demonstrated strong learning orientation, persistence, and innovative behaviors in improving teaching practices. Meanwhile, moderate motivation tended to fluctuate, influenced by administrative burdens, limited time, and work demands. These findings highlight that mastery motivation is multidimensional and shaped by individual, social, and institutional factors. This study is expected to broaden understanding of professional motivation among early childhood teachers, provide empirical foundations for educational policies and sustainable teacher competency development programs, and open opportunities for further, more in-depth research